2012
DOI: 10.1002/we.528
|View full text |Cite
|
Sign up to set email alerts
|

On the use of a linear microphone array to measure wind turbine aerodynamic noise

Abstract: A linear microphone array is shown to be a simple tool to locate aerodynamic sound sources on a horizontal axis wind turbine. This paper discusses the capabilities and limitations of a linear microphone array to locate sound sources and measure aerodynamic noise on the blades of a horizontal axis wind turbine rotor. Compared with a planar microphone array, a linear array requires fewer microphones to achieve the same resolution, a simpler structure to support it and a simpler signal processing algorithm. For a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…It has many applications such as for high-speed train [37], flying aircraft [38 -39] and wind turbine [7,8,10,12,40,41], etc.. A microphone array is composed of a number of microphones, the phase and amplitude of acoustic signal received by each microphone may be different due to their different distance from noise sources. Then the difference of phase and amplitude can be employed by some post processing algorithm to locate the positions of noise sources.…”
Section: Detection Of Noise Sources By Microphones Array Techniquementioning
confidence: 99%
“…It has many applications such as for high-speed train [37], flying aircraft [38 -39] and wind turbine [7,8,10,12,40,41], etc.. A microphone array is composed of a number of microphones, the phase and amplitude of acoustic signal received by each microphone may be different due to their different distance from noise sources. Then the difference of phase and amplitude can be employed by some post processing algorithm to locate the positions of noise sources.…”
Section: Detection Of Noise Sources By Microphones Array Techniquementioning
confidence: 99%
“…An airfoil cross-sectional analysis of the blade trailing edge with and without a 3 mm gap crack defect successfully explained that blade trailing edge cracking is the cause of the accompanying acoustically sharp "whistling sound". Genescà et al [130] analyzed the differences between the noise signals of rotor blades with three different surface treatments using a linear microphone array. They found that the blade surface shedding sound pressure level was the highest.…”
Section: Introduction Of Wind Power Blade Aerodynamic Noisementioning
confidence: 99%
“…Broadband aerodynamic blade noise is the dominant noise source of modern large‐scale wind turbines. Wind turbine noise (WTN) measurements using a linear microphone array outdoors have shown that the noise is mainly generated when the blades go downward and in the outer 25% of the blade span . Therefore, a number of research studies have been dedicated to the design and testing of highly efficient and low‐noise airfoils for wind turbine applications .…”
Section: Introductionmentioning
confidence: 99%
“…Broadband aerodynamic blade noise is responsible for the amplitude modulation (AM) observed mainly in large turbines, that is, a pulsating broadband sound . This AM, commonly referred to as ‘swishing’, ‘whooshing’ or ‘pulsating’ noise, is currently considered to be the main cause of annoyance for residents living near wind farms .…”
Section: Introductionmentioning
confidence: 99%